Analisis Kebutuhan Infrastruktur Di Perbatasan Pulau Marore, Kabupaten Kepulauan Sangihe - Deysi Gatot; Raymond Tarore; Amanda Sembel (Sabua : Jurnal Lingkungan Binaan dan Arsitektur, 2021)
Infrastructure development has a vital role in fulfilling people's basic rights. The availability of infrastructure can have an effect on increasing Marore Island people's access to resources so as to increase access to resource productivity which in turn encourages economic growth. So it is necessary to do research on the analysis of infrastructure needs at the border of Marore Island, Sangihe Islands Regency, where this research aims to identify the existing infrastructure conditions on Marore Island and analyze the infrastructure needs on Marore Island as a national strategic area. The variables to be analyzed in this study include roads, electricity, telecommunications, clean water, waste water, solid waste, drainage, environmental facilities, educational facilities, health facilities, socio-cultural facilities, public serviceÂ facilities and open space facilities using the distribution analysis method. frequency, comparison of minimum service standards (SPM), analysis of fulfillment of needs and spatial analysis. Based on the results of research and discussion regarding the analysis of infrastructure needs at the border of Marore Island, Sangihe Islands Regency, the conclusion that can be obtained is that the existing conditions of each infrastructure are available, but there are still some damaged infrastructure such as environmental facilities (markets), equipment desalination (distillation of salt water into fresh water), PLTS (solar power plant), ice storage equipment for fishermen, telecommunication tower transmitters and connecting roads between eastern settlements to western settlements. So it needs repairs again. Keywords: Border Areas, Infrastructure, Spatial Analysis